Analisa Pengaruh Servant Leadership terhadap job performance karyawan di Hotel X Surabaya - Hariyanto Liman; Nikolas Leon Yaphar; Deborah Christine Widjaja (Jurnal Hospitality dan Manajemen Jasa, 2017)
Abstrak - Analisa Pengaruh Servant Leadership Terhadap Job Performance Karyawan Di Hotel X Surabaya Penelitian ini bertujuan untuk mengetahui manfaat dan dampak servant leadership terhadap job performance karyawan di Hotel X Surabaya. Dimensi servant leadership yang digunakan dalam penelitian ini adalah emotional healing, creating value for the communtiy, conceptual skills, empowering, helping subordinate grow and succeed, putting subordinate first, behaving ethically. Teknik analisis yang digunakan adalah Partial Least Square (PLS). Hasil dari penelitian ini menemukan bahwa dimensi servant leadership putting subordinate first yang paling berpengaruh secara positif dan signifikan terhadap job performance. Servant leadership memiliki pengaruh yang kecil terhadap job performance karyawan.Abstract - Analysis of the Influence of Servant Leadership on Employee Job Performance Hotel X Surabaya The study is intended to determine the influence of servant leadership on employee job performance at Hotel X Surabaya. Servant leadership dimensions used in this study are emotional healing, creating value for the community, conceptual skills, empowering, helping subordinate grow and succeed, putting subordinate first, behaving ethically.The analysis technique used is Partial Least Square (PLS). The result of this study show that the dimension of servant leadership, putting subordinate first has the most dominant influence on job performance. Moreover servant leadership has little impact on the job performance of the employees.